Improving the Ability to Read Aloud Syllables and Words with Correct Pronunciation through the Problem Based Learning Model at MIS Al-Ghuraba - Inayah, Siti Nur; Hartini (MANDAILING GLOBAL EDUKASIA, 2025)
As for the results of the teacher's observation in class, the ability to read aloud syllables and words with the correct pronunciation, grade I students of MIS Al-Ghuraba showed the ability to read aloud syllables and words with low proper pronunciation, this was shown to be a low daily score or did not reach the KKM. The KKM that is expected in the content of the KD Indonesian Reading aloud syllables and words with the correct pronunciation is 70 so the student score should be ≥ 70. Yesterday's daily score, only 6 students or only 30% achieved scores above the KKM, the rest carried out remidi to achieve scores above the KKM. From the results of the interview, the teacher took the initiative to use a learning model that is not usually used in the classroom, namely using the problem based learning model. This class action research was carried out at MIS Al-Ghuraba, in grade I with a total of 20 students. The population of this study is all MIS Al-Ghuraba students for the 2023/2024 school year. Data collection techniques consist of test and non-test techniques. The results of the pre-cycle research can be found that only 6 students (KKM=70) complete their scores, while 14 students (70%) do not complete. So that the researcher seeks to improve the learning process better in the first cycle by making and compiling a more perfect learning improvement plan. Based on the data of the formative test scores after the improvement of cycle 1, it can be said that there is an increase in learning outcomes. This is shown by the increase in the results of the formative test, which was originally only 6 students (30%) to 15 students (75%). Based on observations in Cycle II, students are active in participating in learning and in carrying out teachers' duties well. It turns out that through using the problem-based learning model in improving student learning outcomes, it has been in accordance with the expected plan.